Impact of omega-3 fatty acids supplementation on lipid levels in pregnant women with previous pregnancy losses: a retrospective longitudinal study - Mu, Fangxiang; Wang, Weijing; Liu, Lin; Hu, Ning; Wang, Fang (Frontiers in Nutrition, 2024)
Objective: This research aims to investigate the impact of omega-3 fatty acids supplementation on the lipid levels of pregnant women who have experienced pregnancy losses.Methods: This retrospective study analyzed data from pregnant women with previous pregnancy losses from two medical centers. Their lipid profiles were measured at least twice during pregnancy. According to the use of omega-3 soft gel capsules, participants were divided into the omega-3 group and the control group. We assessed the relationship between omega-3 fatty acids supplementation and longitudinal lipid levels during pregnancy using generalized estimating equations (GEE). Subsequently, we conducted subgroup analyses to delineate the profile of beneficiaries who received omega-3 fatty acids based on body mass index (BMI), age, menstrual regularity, number of previous pregnancy losses, number of previous live births, and educational level.The omega-3 group included 105 participants, while the control group comprised 274 participants. Women in the omega-3 group started supplementation between 3.43 and 17.14 weeks of gestation. According to GEE analysis, supplementing omega-3 fatty acids significantly reduced triglyceride (TG) levels during pregnancy (adjusted β = -0.300, 95% CI -0.445 to -0.154, P < 0.001). No associations between omega-3 fatty acids supplementation and total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), or high-density lipoprotein cholesterol (HDL-C) levels were observed. Subgroup analyses revealed that omega-3 fatty acids supplementation was related to a reduction in TG levels among pregnant women with age of ≤ 35 years, a normal BMI (18.5-24.9 kg/m 2 ), 1-2 previous pregnancy losses, no previous live births, or an educational level above high school.Conclusion: Supplementation with omega-3 fatty acids may significantly reduce TG levels, yet it does not seem to improve TC, LDL-C, or HDL-C levels in pregnant women with previous pregnancy losses.